2009
DOI: 10.1016/j.jconrel.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A designer biomimetic vector with a chimeric architecture for targeted gene transfer

Abstract: Designer biomimetic vectors are genetically engineered biomacromolecules that are designed to mimic viral characteristics in order to overcome the cellular barriers associated with the targeted gene transfer. The vector in this study was genetically engineered to contain at precise locations: a) four tandem repeating units of N-terminal domain of histone H2A to condense DNA into stable nanosize particles suitable for cellular uptake, b) a model targeting motif to target HER2 and enhance internalization of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 25 publications
2
62
0
Order By: Relevance
“…Nevertheless GALA has been utilized in several multi-functional systems as a discrete endosomal-disrupting motif. For example, the GALA peptide was incorporated into a biomimetic vector that also had four repeats of histone proteins to condense DNA, a targeting motif for HER2 and a cathepsin substrate that acts as an intracellular cleavage site (61) . Studies demonstrated that positioning GALA on the N-terminus of the multifunctional vector ensured fusogenic amphipathic activity.…”
Section: Endosomal Escapementioning
confidence: 99%
“…Nevertheless GALA has been utilized in several multi-functional systems as a discrete endosomal-disrupting motif. For example, the GALA peptide was incorporated into a biomimetic vector that also had four repeats of histone proteins to condense DNA, a targeting motif for HER2 and a cathepsin substrate that acts as an intracellular cleavage site (61) . Studies demonstrated that positioning GALA on the N-terminus of the multifunctional vector ensured fusogenic amphipathic activity.…”
Section: Endosomal Escapementioning
confidence: 99%
“…The fusion vector was equipped with a HER2 targeting affibody, a DNA condensing motif derived from human histone H2A, and the fusogenic peptide GALA [120,121]. The vector in combination with SR39 and GCV showed 80% toxicity to SKOV-3 cancer cells in vitro.…”
Section: Entry Targeting: Vector-mediated Suicide Gene Therapymentioning
confidence: 99%
“…Generally, DBVs possess a DNA-condensing motif (DCM), endosomal disruption motif (EDM), nuclear localisation motif (NLS) and targeting motif (TP) [15,135].…”
Section: Designer Biomimetic Vectorsmentioning
confidence: 99%